Comparison of Commercially Available Thermostable DNA Polymerases with Reverse Transcriptase Activity in Coupled Reverse Transcription Polymerase Chain Reaction Assays - Evgeniya V. Smirnova; Konstantin A. Blagodatskikh; Ekaterina V. Barsova; Dmitriy A. Varlamov; Vladimir M. Kramarov; Konstantin B. Ignatov (Methods and Protocols, 2025)
Reverse transcription polymerase chain reaction (RT-PCR) is an important tool for the detection of target RNA molecules and the assay of RNA pathogens. Coupled RT-PCR is performed with an enzyme mixture containing a reverse transcriptase and a thermostable DNA polymerase. To date, several biotechnological companies offer artificial thermostable DNA polymerases with a built-in reverse transcriptase activity for use in the coupled RT-PCR instead of the enzyme mixtures. Here, we compared the artificial DNA polymerases and conventional enzyme mixtures for the RT-PCR by performing end-point and real-time RT-PCR assays using severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV2) RNA and endogenous mRNA molecules as templates. We found that the artificial enzymes were suitable for different RT-PCR applications, including SARS-CoV2 RNA detection but not for long-fragment RT-PCR amplification.